2018
DOI: 10.1097/icu.0000000000000441
|View full text |Cite
|
Sign up to set email alerts
|

Cataract surgery in ocular surface diseases

Abstract: Cataract surgery in ocular surface diseases needs careful preoperative, intraoperative and postoperative planning. Performed in a staged manner under favorable ocular environment, it has good visual outcomes and can improve the quality of life in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 46 publications
0
29
0
1
Order By: Relevance
“…Cataract surgery is the most frequently performed surgical procedure in developed countries 1,2 , providing significant long-term and cost-effective improvements in the quality of life of patients 3 . In the last decades, advances in cataract surgery techniques and new technological developments have led to improved patient safety and satisfaction, resulting in high expectation regarding the refractive outcomes 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Cataract surgery is the most frequently performed surgical procedure in developed countries 1,2 , providing significant long-term and cost-effective improvements in the quality of life of patients 3 . In the last decades, advances in cataract surgery techniques and new technological developments have led to improved patient safety and satisfaction, resulting in high expectation regarding the refractive outcomes 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In an animal study, EK and other ocular surface diseases were found to result from the abnormal tear function after cataract surgery [ 13 ]. As Sangwan et al [ 14 ] reported, surgeries for cataract combined with ocular surface diseases needed careful preoperative, intraoperative, and postoperative planning to prevent postoperative epitheliopathy. In this study, 60.67% of all patients with EK after cataract surgery were more than 70 years old, with an average age of 69.85 ± 9.61 years.…”
Section: Discussionmentioning
confidence: 99%
“…A cataract is the first kind of blinding eye disease in China and even in the whole world. Usually, the metabolic disorder of the patient's eye lens leads to degeneration of lens protein, which leads to intraocular lens opacity (1). Cataracts mostly occur in middle-aged and elderly people over 50 years old, which can be caused by age, decreased immunity, radiation, drugs, poisoning, and other factors.…”
Section: Introductionmentioning
confidence: 99%